Adolescent narrative comments in assessing medical students. (14th June 2017) - Tan, April; Hudson, Alexandra; Blake, Kim
Summary: Background: Adolescent medical interviewing is a difficult topic to teach and assess. Programmatic assessment has been gaining interest in medical teaching, and shifts the mode of assessment from the traditional assessment of learning (e.g. written exams) to the assessment for learning (e.g. feedback). The Structured Communication Adolescent Guide (SCAG) is a programmatic assessment tool that allows an adolescent patient to provide three types of feedback (written, numeric, grade) to a medical student in an authentic clinical workplace. Methods: We conducted a qualitative analysis of written narrative feedback from SCAGs completed by non‐standardised adolescent patients interviewed by third‐year medical students. SCAG numerical scores and grades were compared between the positive and the negative written narrative feedback. Results: Thirty‐seven (50%) of 74 SCAGs had written narrative feedback. 'Approachable' and 'confidentiality concerns' were the most common positive and negative written comments, respectively. The 'teen‐only communication' SCAG section, containing the HEADSS (Home, Education, Activities, Drugs, Suicide, Sex) portion of the interview, had the highest number of negative comments. All of the positive comments had A grades (100%), whereas the negative comments had A (58%), B (37%) and C (5%) grades. The 'teen‐only communication' and 'initiating the interview' SCAG sections had significantly lower numerical scores assigned to negative feedback (p = 0.023, p < 0.001). Adolescent medical interviewing is a difficult topic to teach and assess Discussion: Confidentiality concerns remain a top priority for undergraduate medical education training in adolescent patient interviewing. Written narrative feedback is extremely valuable as teens can provide both positive and negative comments. This is in contrast to adolescent patients most often over‐inflating grades or scores to all learners, which can mislead the student.